2020
DOI: 10.1007/s11356-020-10112-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of particulate matter 2.5 on the risk of preeclampsia: an updated systematic review and meta-analysis

Abstract: There is increasing and inconsistent evidence of a linkage between maternal exposure to particulate matter 2.5 (PM2.5) and preeclampsia. Therefore, this study was conducted to investigate this relationship. Electronic databases including PubMed, Embase, Web of Science, and Cochrane Library were searched to identify articles published from inception to March 23, 2020, which showed a correlation between PM2.5 and preeclampsia. Finally, 9 of 523 initial studies were deemed eligible for inclusion. A random effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…Thus, exposure to can not only contribute to a pregnancy becoming a high-risk pregnancy—given that past work has shown that it is associated with pregnancy conditions, such as gestational diabetes and preeclampsia ( Tang et al. 2020 ; Yu et al. 2020 )—but also, based our findings, may predispose such high-risk individuals to its adverse health effects.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, exposure to can not only contribute to a pregnancy becoming a high-risk pregnancy—given that past work has shown that it is associated with pregnancy conditions, such as gestational diabetes and preeclampsia ( Tang et al. 2020 ; Yu et al. 2020 )—but also, based our findings, may predispose such high-risk individuals to its adverse health effects.…”
Section: Discussionmentioning
confidence: 62%
“…This matches the time-window of exposure investigated in our study. 71 Our analysis has several strengths. The MIREC Study is a prospective, multisite pregnancy cohort study, and is well positioned to study the impact of ambient air pollution on maternal health.…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is a pregnancy pathology associated with placental dysfunction and defined by a new onset of hypertension with or without proteinuria after 20 weeks of gestation ( 70 ). A recent meta-analysis performed with data up to March 2020, summarized 9 cohort studies and concluded that maternal exposure to PM 2.5 during the third trimester of pregnancy elevates the risk of preeclampsia ( 71 ). Some epidemiological studies, use the distributed lag linear model, which is a statistical analysis model that distributes the effect of a single exposure event over a specific time period, in order to estimate the lag effect between exposure to ambient air pollutants and a health outcome ( 72 ).…”
Section: Air Pollution Exposure During Pregnancymentioning
confidence: 99%